Violence against Women On the implementation of the Istanbul Convention in Denmark, Finland & Austria - Lange, Katrin; Molter, Sarah; Wittenius, Marie (Berlin, 2020)
The Council of Europe Convention on Preventing and Combating Violence against Women and Domestic Violence (Istanbul Convention) is a treaty of international law that entered into force on 1 August 2014. The Convention contains binding regulations on the protection of women against all forms of violence. The Istanbul Convention obliges the States Parties to provide a needs-based, comprehensive, well-equipped and financially guaranteed support system. The specialist support services, as specified in Article 22, represent a central building block of this help system. In Articles 23 and 25, obligations related to shelters and support for victims of sexual violence are specified. In this working paper, the Observatory examines the implementation of the Istanbul Convention to protect and support women affected by violence in a comparison between Denmark, Finland and Austria.
Keywords: Gewalt gegen Frauen; Gleichstellungspolitik; Europäische Union; Menschenrechte; 320 Politikwissenschaft; Istanbul Konvention; Österreich; Dänemark; Finnland; Europarat